Review of recent publications (Studies in 20th & 21st Century Literature, 2003)
Bishop, Michael, ed. Women's Poetry in France, 1965-1995. by Martine Antle Black, Stanley. Juan Goytisolo and the Poetics of Contagion: The Evolution of a Radical Aesthetic in the Later Novels by Bernardo Antonio González Fachinger, Petra. Rewriting Germany from the Margins: "Other" German Literature of the 1980s and 1990s by Cornelius Partsch Graham-Jones, Jean. Exorcising History: Argentine Theater under Dictatorship by Daniel Altamiranda Wishnia, Kenneth J. Twentieth-Century Ecuadorian Narrative by Adelaida López de Martínez
Keywords: Review; Women' s Poetry in France; 1965-1995; Martine Antle; Juan Goytisolo and the Poetics of Contagion: The Evolution of a Radical Aesthetic in the Later Novels; Bernardo Antonio González; Rewriting Germany from the Margins: " Other" German Literature of the 1980s and 1990s; Cornelius Partsch; Exorcising History: Argentine Theater under Dictatorship; Daniel Altamiranda; Michael Bishop; Stanley Black; Petra Fachinger; Jean Graham-Jones; Kenneth J. Wishnia; Twentieth-Century Ecuadorian Narrative; Adelaida López de Martínez